Application Of The Expert System Of Certainty Factor Methods In Diagnosing Thyroid Disease - Ellanda Purwawijaya; Fithrie Soufitri; Fahmi Ruziq; Dinur Syahputra (INFOKUM, 2021)
Thyroid gland disease or what is called hyperthyroidism is a disease that is often found in the community. The body's need for thyroid hormone is needed to control body growth and process food metabolism into energy. An overactive thyroid gland produces thyroid hormone which causes high levels of thyroid hormone in the blood. This condition is known as hyperthyroidism. In the medical world, to be able to diagnose hyperthyroidism is difficult, because the symptoms of hyperthyroidism vary greatly, depending on the rise and fall of thyroid hormones. From the above problems, a technology utilization is needed to reduce each problem and implement it into an expert system. An expert system is a branch of artificial intelligence that uses special knowledge/knowledge to solve problems at the human expert/expert level. Expert systems have been developed in various sciences, one of which is in the field of medicine to diagnose diseases. The expert system used to determine the diagnosis of the disease will help confirm the diagnosis and provide advice and therapy in the treatment of the disease. The test results "Expert System Diagnosing Hyperthyroid Disease Using the Certainty Factor Method" show that this expert system can diagnose hyperthyroidism according to the answers given by the user with an accuracy value of 100%.